Phase‐Modulated Scattering Manipulation for Exterior Cloaking in Metal–Dielectric Hybrid Metamaterials. Issue 39 (5th August 2019) - Zhang, Fuli; Li, Chang; Fan, Yuancheng; Yang, Ruisheng; Shen, Nian‐Hai; Fu, Quanhong; Zhang, Weihong; Zhao, Qian; Zhou, Ji; Koschny, Thomas; Soukoulis, Costas M.
Abstract: Artificially structured metamaterials with metallic or dielectric inclusions are extensively studied for exotic light manipulations via controlling the local‐resonant modes in the microstructures. The coupling between these resonant modes has drawn growing interest in recent years due to the advanced functional metamaterial making the microstructures more and more complex. Here, the suppression of magnetic resonance of a dielectric cuboid, an analogue to the scattering cancellation effect or radiation control system, realized with an exterior cloaking in a hybrid metamaterial system, is demonstrated. Furthermore, the significant modulation of the absorption of the dielectric resonator in the hybrid metamaterial is also demonstrated. The physical insight of the experimental results is well illuminated with a classical double‐harmonic‐oscillator model, from which it is revealed that the complex coupling, i.e., the phase of coupling coefficient, plays a crucial role in the overall response of the metal–dielectric hybrid system. The proposed design strategy is anticipated to form a more straightforward and efficient paradigm for practical applications based on radiation control via versatile mode couplings. Abstract : A hybrid metamaterial made of a coupled dielectric cuboid and metallic structure is proposed for a novel radiation/scattering control platform. The suppression of magnetic resonance of a dielectric cuboid is experimentally realized with an exterior metallic cloaking. It is found that the complex coupling, i.e., the phase of coupling coefficient, plays a crucial role in the overall response of the metal–dielectric hybrid metamaterial.